Silicon Improves Cold and Freezing Tolerance in Pea - Ufuk Akçay; Hande Nur Kumbul; İbrahim Ertan Erkan (Turkish Journal of Agriculture: Food Science and Technology)
The most significant crop losses worldwide occur due to unfavorable temperatures such as heat, drought, cold, and freezing. Minerals like silicon can play important roles in the growth, development, and stress responses of plants. In this study, changes in stem/root length, dry weight, relative water content and silicon content, of peas under cold and freezing stress, as well as antioxidant system indicators such as proline, malondialdehyde, hydrogen peroxide, and chlorophyll levels, ion leakage, and the expressions of genes coding for the topoisomerase TOP2 and DNA helicase PDH47 enzymes, which play important roles in the replication, transcription, and repair of DNA molecules, were examined in root and stem tissues in the presence of two different concentrations of silicon. The results of the study showed that silicon application under cold and freezing stresses has induced various changes in pea metabolism, including increases in cell membrane integrity parameters and superoxide dismutase enzyme activity, as well as increase in the expressions of TOP2 and PDH47 genes. These changes have been found to have positive effects on the pea cold and freezing tolerance.